Timothy H. Lim and John H. Collins, eds., The Oxford Handbook of the Dead Sea Scrolls (Oxford: Oxford University Press, 2010, Paperback edition, 2012). Pp. xviii + 785. $ 45. ISBN 978-0-19-966308-8 - Drawnel, Henryk (The Biblical Annals, 2015)
Book review